2017
DOI: 10.3390/w9050346
|View full text |Cite
|
Sign up to set email alerts
|

Summer Season Water Temperature Modeling under the Climate Change: Case Study for Fourchue River, Quebec, Canada

Abstract: Abstract:It is accepted that human-induced climate change is unavoidable and it will have effects on physical, chemical, and biological properties of aquatic habitats. This will be especially important for cold water fishes such as trout. The objective of this study is to simulate water temperature for future periods under the climate change situations. Future water temperature in the Fourchue River (St-Alexandre-de-Kamouraska, QC, Canada) were simulated by the CEQUEAU hydrological and water temperature model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…Although Kwak et al (2017) reported a relatively small increase in median June temperature (0.2 -0.7 °C increase in mean June temperature by 2096), the results of our study are broadly consistent with the findings of Daigle et al (2015;0.7-2.7 °C increase in seven-day maximum temperature by 2065), thus adding credence to our projected increase in annual maximum and summer minimum river temperature towards 2100. However, both Kwak et al (2017) and Daigle et al (2015) were conducted in substantially smaller watersheds than the SJR, so limited inferences can be drawn as to their comparability.…”
Section: Ecologically Relevant Temperature Metricssupporting
confidence: 90%
See 1 more Smart Citation
“…Although Kwak et al (2017) reported a relatively small increase in median June temperature (0.2 -0.7 °C increase in mean June temperature by 2096), the results of our study are broadly consistent with the findings of Daigle et al (2015;0.7-2.7 °C increase in seven-day maximum temperature by 2065), thus adding credence to our projected increase in annual maximum and summer minimum river temperature towards 2100. However, both Kwak et al (2017) and Daigle et al (2015) were conducted in substantially smaller watersheds than the SJR, so limited inferences can be drawn as to their comparability.…”
Section: Ecologically Relevant Temperature Metricssupporting
confidence: 90%
“…Physiographic data necessary to run CEQUEAU's hydrological model component were assembled from a range of GIS databases. Elevations were derived from a 1 arc-second (~25 m) SRTM digital elevation model (Farr et al, 2007), while raster land use data used to compute forest and bare soil cover were obtained from the North American Land-Change Monitoring System (Latifovic et al, 2012). Percentage cover of waterbodies and wetlands were obtained from vector shapefiles downloaded from the Government of New Brunswick's GeoNB geospatial data portal (http://www.snb.ca/geonb1/e/index-E.asp).…”
Section: Study Areamentioning
confidence: 99%
“…Two climate change scenarios were considered in this study: RCP 4.5 and RCP 8.5 scenarios. A general circulation model (GCM), with a basis in climate-assessment studies [32][33][34], provides the general circulation of the Earth's atmosphere. Although the spatial coverage is global, the grid size is too coarse for modelling wave forcings (i.e.…”
Section: First Step: Process-based Dynamical Modellingmentioning
confidence: 99%
“…In addition to long-term synoptic assessment, an approach that is likely to become important to projecting the future of lake thermal properties in a warming world, is coupled modeling. In this special issue, Kwak et al [13] used a model that can simulate hydrological and thermal responses of water bodies to warming, and coupled it with output from the Coupled Model Inter-Comparison Project Phase 5 (CMIP5) Global Circulation Models (GCMs). They evaluated the projected effects of three future climate scenarios on the Fourchue River, Quebec, Canada.…”
Section: Lake Warmingmentioning
confidence: 99%